Optimasi Kendali PID berbasis IoT pada Oven Listrik untuk Pengeringan Rempah yang Presisi - Pratama, Bambang; Salamah, Irma; Lindawati, Lindawati (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Unstable spice drying can reduce active compound content by up to 30% and increase the risk of microbial contamination by up to 40%, while conventional temperature control does not ensure thermal stability. This study aims to develop an IoT-based drying system using a PID algorithm to maintain temperature stability and allow remote monitoring and control. The research followed the waterfall model, starting from needs analysis, hardware and software design, PID implementation using a trial-and-error approach, IoT application development with Kodular and Firebase, system integration, and full system performance testing. Key components include the DS18B20 temperature sensor, ESP32, heating element, and IoT platform. Software testing used the black box method, while hardware testing evaluated performance through overshoot, steady-state error, settling time, disturbance simulation, and comparison with the on-off control method. The resulting system automatically regulates temperature with a PID algorithm and enables real-time monitoring via mobile devices. Testing showed the PID system was more stable than the on-off method, with overshoot <4°C, steady-state error <1.5°C, settling time of ±750 seconds, and quick response to disturbances. The mobile application operated reliably without errors, enhancing the quality and precision of the spice drying process.